Prevalence and Determinants of a Blunted Parathyroid Hormone Response in Young Saudi Women with Vitamin D Deficiency: A Cross-Sectional Study - Hanan Al Kadi (International Journal of Endocrinology)
Vitamin D deficiency is highly prevalent among the Saudi population. Increased parathyroid hormone (PTH) secretion is an appropriate homeostatic response to correct the resultant hypocalcemia. However, not all vitamin D deficiency patients have increased PTH levels. This study determined the prevalence of a blunted PTH response to vitamin D deficiency among apparently healthy young Saudi women and assessed anthropometric and biochemical factors associated with this response by performing a secondary analysis of data obtained from a cross-sectional study conducted at the “Center of Excellence for Osteoporosis research.” Overall, 315 women (aged 20–45 years) with vitamin D deficiency (serum 25-hydroxyvitamin D (25(OH)D) levels <30 nmol/L) were included. They were divided into two groups according to the laboratory cutoff value of PTH (<7 or ≥7 pmol/L), and anthropometric and biochemical characteristics of both groups were compared. Women with a blunted PTH response (n = 62, 19.7%) had a significantly lower body mass index (BMI) (P<0.001) and smaller waist circumference (P=0.001). They also had significantly higher serum 25(OH)D (P=0.001), corrected serum calcium (P<0.001), and phosphate (P=0.003) levels than those with an elevated PTH response (n = 253, 80.3%). Multiple logistic regression analysis showed that lower BMI (OR = 0.925; 95% CI: 0.949–0.987) and higher 25(OH)D (OR = 1.068; 95% CI: 1.014–1.124) and serum calcium (OR = 8.600; 95% CI: 1.614–45.809) levels were significantly associated with a blunted PTH response (R2 = 0.178). A blunted PTH response to vitamin D deficiency is mainly observed among women with lower BMI. Higher serum calcium and 25(OH)D levels and lower BMI were significant predictors of a blunted PTH response, which may indicate that these subjects are adapting to lower 25(OH)D levels and maintaining normal calcium levels without the need to increase PTH secretion. The mechanisms underlying this adaptation are unclear, and future studies to explore these mechanisms are warranted.